cGMP as mediator of contractility in papillary muscle from normal and non-insulin dependent diabetic rat myocardium - Upton, Jeanne J (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1999.